PELAKSANAAN KETERBUKAAN INFORMASI OLEH BIDANG INFORMASI DAN KOMUNIKASI PUBLIK DISKOMINFO KABUPATEN GARUT - Mey Irma Rimayanti; Haryadi Mujianto; R. Ismira Febrina (LPPM Universitas ARS, 2021)
This research is motivated by the openness of public information as outlined in Law no. 14 of 2008 has not been fully implemented by Diskominfo Garut Regency. The purpose of this study was to determine the communication made by Diskominfo, the existence of human resources on duty and the attitude of officers in disseminating public information and to know the bureaucratic structure designed by Diskominfo Garut Regency in disseminating public information. This study used descriptive qualitative method. Data collection techniques were carried out by in-depth interviews, observations, literature studies and documentation. Researchers took 10 informants. The results of the study indicate that there has been good communication between the regional organizational units in Garut Regency and Diskominfo. There is still a lack of human resources and work facilities, officers have acted responsibly by complying with regulations related to public information disclosure, and there is already a bureaucratic structure and SOP in disseminating public information.